Steel sheet, steel member, and method for manufacturing steel sheet
Patent Information
- Application Number
- CN202580023579.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-28
- Filing Date
- 2025-03-28
- Publication Date
- 2026-10-30
AI Technical Summary
[0008]然而,在专利文献1~4中,虽然考虑了钢板的成型性,但对于在成型为构件后受到轴向压溃变形时的断裂的产生还有进一步研究的余地
根据本发明的上述方式,能够提供一种钢板及其制造方法、以及使用该钢板得到的能够抑制受到轴向压溃变形时的断裂的钢构件,所述钢板具有高强度且优异的伸长率,在成型为构件后受到轴向压溃变形时能够抑制构件的断裂。
Smart Images

Figure FT_1 
Figure FT_2 
Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to steel plates, steel components, and methods for manufacturing steel plates.
[0002] This application claims priority based on Japanese Patent Application No. 2024-053452 filed on March 28, 2024, the contents of which are incorporated herein by reference. Background Technology
[0003] In recent years, from the perspective of limiting greenhouse gas emissions as part of global warming countermeasures, there has been a demand to improve the fuel efficiency of automobiles. To achieve lighter vehicle bodies and improved crash safety, the application of high-strength steel in automotive components has been gradually expanding. Recently, the demand for ultra-high-strength steel with tensile strengths exceeding 980 MPa has been increasing.
[0004] On the other hand, in order to make steel sheets into automotive parts, they are stamped, welded, etc. Therefore, steel sheets supplied for automotive parts are required not only to have strength, but also to have various workability requirements during the part forming process, such as stamping formability and weldability. For example, from the point of view of stamping formability, steel sheets are mostly required to have excellent elongation (total elongation in tensile tests: EL).
[0005] However, as steel plates become stronger, the total elongation (EL) tends to decrease, making it difficult to simultaneously ensure high levels of strength and total elongation.
[0006] In contrast, for example, as shown in Patent Documents 1-4, TRIP steel sheets (Transformation Induced Plasticity) are known to utilize the phase transformation of retained austenite to induce plasticity, thus achieving both high strength and workability.
[0007] However, in recent years, there has been a demand to further suppress fracture when components are subjected to axial crushing deformation after being formed into impact deformation components, by improving the properties of the steel plate itself.
[0008] However, although the formability of steel plates was considered in patent documents 1-4, there is still room for further research on the occurrence of fracture when subjected to axial crushing deformation after being formed into components.
[0009] Existing technical documents Patent documents Patent Document 1: International Publication No. 2013 / 051238 Patent Document 2: Japanese Patent Application Publication No. 2006-104532 Patent Document 3: Japanese Patent Application Publication No. 2007-262494 Patent Document 4: International Publication No. 2018 / 179386 Summary of the Invention
[0010] The problem that the invention aims to solve As mentioned above, there is still room for further research on the suppression of fracture when steel plates are subjected to axial crushing deformation after being formed into components such as impact-deformable members.
[0011] Therefore, the objective of this invention is to provide a steel plate and a method for manufacturing the same, and a steel member obtained using the steel plate that can suppress fracture when subjected to axial crushing deformation, the steel plate having high strength and excellent elongation, and being able to suppress fracture of the member when subjected to axial crushing deformation after being formed into a member.
[0012] Methods for solving problems The inventors conducted research on whether the fracture of a component under axial crush deformation can be suppressed by the composition (chemical composition, microstructure, etc.) of the steel plate.
[0013] The results showed that in steels with a microstructure dominated by bainite and / or martensite and containing retained austenite, fracture could be suppressed by controlling the distribution of retained austenite.
[0014] Furthermore, steel plates are processed into components, which are then further welded (spot welded, etc.) to become other components as needed. Even in such welded components, the proportion of the welded portion and the HAZ portion is small. Therefore, if the other parts (non-welded portions) have a structure that can suppress the fracture of the component, the fracture suppression effect of the component can be obtained.
[0015] However, the HAZ portion deteriorates due to the heat of welding and is sometimes prone to fracture. Therefore, by having a structure in the HAZ portion that can also suppress component fracture, a further preferred component fracture suppression effect can be obtained.
[0016] Therefore, the inventors also studied the suppression of fracture during axial crushing deformation at the spot weld of the component. The results showed that by controlling the concentration distribution of Mn and Si during the stage of the steel plate becoming the raw material, fracture of the component in the HAZ region could be suppressed.
[0017] This invention was made in view of the above-mentioned insights. The main points of this invention are as follows.
[0018] [1] A steel plate according to one aspect of the present invention comprises, by mass%, C: 0.08~0.20%, Si: 0.50~1.80%, Mn: 2.00~3.50%, P: less than 0.050%, S: less than 0.0100%, Al: 0.001~1.000%, Ti: 0.001~0.100%, B: 0.0005~0.0050%, N: less than 0.0100%, O: less than 0.0100%, Cr: 0~1.00%, Mo: 0~1.00%, Cu: 0~1.00%, Ni: 0~1.00%, Co: 0~1.00%, W: 0~1.00%, Ta: 0~1.00%, Sn: 0 ~1.00%, Sb: 0~0.50%, Nb: 0~0.200%, V: 0~1.00%, As: 0~0.10%, Zn: 0~1.0000%, Ca: 0~0.0100%, Mg: The chemical composition of Fe and impurities, measured in area % at a position 1 / 4 of the plate thickness from the surface towards the plate thickness, includes: retained austenite: 3-10%, ferrite: 0-10%, pearlite: 0-5%, and martensite and bainite. The microstructure at this position, measured in area % from the surface towards the plate thickness, comprises: retained austenite: 3-10%, ferrite: 0-10%, pearlite: 0-5%, and martensite and bainite. The total percentage is 75-97%. In a cross-section parallel to the thickness direction, an 80μm x 80μm area centered at the 1 / 4 thickness position along the thickness direction and another 80μm area perpendicular to the thickness direction is divided into 16 20μm x 20μm portions. When calculating the area ratio of retained austenite in each of these portions, the standard deviation of the area ratio of retained austenite in each portion is set as σ1, and the average is set as γ. ave At that time, σ1 / γ ave It is below 0.20.
[0019] [2] According to the steel plate described in [1], the standard deviation σ2 of the mass percentage concentrations [Mn] and [Si] of the Mn and Si concentrations [Si] at each of the multiple measurement points measured by EPMA in the 35μm×50μm region of the section parallel to the thickness direction of the plate and the range of 1 / 8 to 3 / 8 thickness centered at the 1 / 4 thickness position can be less than 0.80.
[0020] MS=[Mn]+(2 / 3)×[Si]…(1) [3] The steel plate according to [1] or [2] may have a hot-dip galvanized layer or an alloyed hot-dip galvanized layer on the above surface.
[0021] [4] Another aspect of the steel component of the present invention has a steel plate including an unprocessed portion, wherein the unprocessed portion comprises, by mass%, C: 0.08~0.20%, Si: 0.50~1.80%, Mn: 2.00~3.50%, P: less than 0.050%, S: less than 0.0100%, Al: 0.001~1.000%, Ti: 0.001~0.100%, B: 0.0005~0.0050%, N: less than 0.0100%. , O: 0.0100% or less, Cr: 0~1.00%, Mo: 0~1.00%, Cu: 0~1.00%, Ni: 0~1.00%, Co: 0~1.00%, W: 0~1.00%, Ta: 0~ 1.00%, Sn: 0~1.00%, Sb: 0~0.50%, Nb: 0~0.200%, V: 0~1.00%, As: 0~0.10%, Zn: 0~1.0000%, Ca: 0~0.01 The chemical composition of the unprocessed portion, including 0.00%, Mg: 0~0.0100%, Zr: 0~0.0100%, Bi: 0~0.0100%, REM: 0~0.0100%, Hf: 0~0.0100%, and the remainder: Fe and impurities, is as follows: The microstructure of the unprocessed portion at a position representing 1 / 4 of the thickness from the surface in the thickness direction (i.e., the 1 / 4 thickness position) comprises, by area %, 3~10% retained austenite, 0~10% ferrite, 0~5% pearlite, and... Martensite and bainite: 75-97% in total. In a cross-section parallel to the aforementioned thickness direction, an 80μm × 80μm area centered at the aforementioned 1 / 4 thickness position in the aforementioned thickness direction and an 80μm area perpendicular to the aforementioned thickness direction is divided into 16 20μm × 20μm portions. When calculating the area ratio of retained austenite in each of the divided regions, the standard deviation of the area ratio of retained austenite in each of the aforementioned divided regions is set as σ1, and the average is set as γ. ave At that time, σ1 / γ ave It is below 0.20.
[0022] [5] The steel member according to [4] includes a steel plate having a spot weld portion, a HAZ portion surrounding the spot weld portion, and a non-welded portion other than the spot weld portion and the HAZ portion, wherein the non-machined portion is present in the non-welded portion.
[0023] [6] According to the steel member described in [4] or [5], in the above-mentioned non-machined part, the standard deviation σ2 of the MS value of the concentrations of Mn [Mn] and Si [Si] at each of the multiple measurement points measured by EPMA in a 35μm×50μm region of 1 / 8 to 3 / 8 thickness range centered on the above-mentioned 1 / 4 thickness position can be less than 0.80.
[0024] MS=[Mn]+(2 / 3)×[Si]…(1) [7] The steel member according to any one of [4] to [6] may have a galvanized layer or an alloyed hot-dip galvanized layer on the surface of the steel plate.
[0025] [8] Another method for manufacturing a steel plate according to the present invention is the method for manufacturing a steel plate as described in [1], comprising: a continuous casting process, wherein a slab having the chemical composition described in [1] is obtained by continuous casting; a hot rolling process, wherein the slab is heated to a heating temperature and subjected to hot rolling including rough rolling and finish rolling, and then cooled to a coiling temperature and coiled at the coiling temperature to obtain a hot-rolled steel plate; a cold rolling process, wherein the hot-rolled steel plate is pickled and cold-rolled with a cumulative reduction rate of 30-75% as needed to obtain a cold-rolled steel plate; and a heat treatment process, wherein the hot-rolled steel plate or the cold-rolled steel plate is heat-treated, wherein in the hot rolling process, the slab has the chemical composition described in [1]; When the heating temperature is 1200°C or higher, and the number of passes in the finishing rolling is set to n, with the initial pass designated as pass 1 and the final pass as pass n, the inlet temperature of pass n-2 is 950°C or higher, and the outlet temperature of pass n is 900°C or higher. In the finishing rolling, at least one pass exhibits a reduction rate exceeding 25%. The time between each pass (n-2 and n-1, and between n-1 and n) is 0.2 to 1.0 seconds. The time from the end of pass n to the start of cooling is 1.0 to 3.0 seconds. The coiling temperature... The temperature is 200~550℃. During the cooling process up to the coiling temperature, the average cooling rate between 600~750℃ is 20℃ / s or more. The heat treatment process includes a heating process, a first cooling process, a first holding process, a second cooling process, and a second holding process. During the heating process, the hot-rolled steel sheet or the cold-rolled steel sheet is heated to a temperature range of Ac3-20℃ to 950℃ and held in the temperature range for 1~1000 seconds. During the first cooling process, the hot-rolled steel sheet or the cold-rolled steel sheet after the heating process is cooled at an average cooling rate of 10℃ / s or more between 650℃ and 550℃. The hot-rolled steel plate or the cold-rolled steel plate after the first cooling process is cooled to a first cooling stop temperature in the first temperature range of Ms-50℃ to 550℃. During the first holding process, the hot-rolled steel plate or the cold-rolled steel plate after the first cooling process is held in the first temperature range for 20 to 100 seconds. During the second cooling process, the hot-rolled steel plate or the cold-rolled steel plate after the first holding process is cooled to below 200℃. During the second holding process, the hot-rolled steel plate or the cold-rolled steel plate after the second cooling process is heated to a second temperature range of 200 to 420℃. The plate is held in the second temperature range in a manner that satisfies the following formulas (2) and (3).
[0026] [Mathematical Expression 1] [Mathematical Expression 2] Here, t and t in equations (2) and (3) above. f T 、 T max The following are respectively represented.
[0027] t: Elapsed time [seconds] t f End of stay (in seconds) T: Temperature at time t [K] T max The highest temperature reached during residence [K] [9] In the steel plate manufacturing method of [8], in the rough rolling process, the slab is subjected to a reduction rate of more than 20% for more than 3 passes when the slab temperature is above 1050°C, and in the continuous casting process, the casting can be carried out in a manner that satisfies the following formulas (4) and (5).
[0028] [Mathematical Expression 3] [Mathematical Expression 4] Here, τ, τ1, and T in equations (4) and (5) above. S (τ), T C (τ), T L f L M L M δ S L S δ D δ Mn D δ Si The following are represented respectively. T C (τ) is obtained by the above equation (5).
[0029] τ: Elapsed time in seconds since casting began. τ1: T in seconds C (τ) The solidification end temperature T at unit K. δ Time T S (τ): Slab surface temperature in Kelvin over time τ T C (τ): Estimated internal temperature of the slab over time τ, in K. T LSolidification onset temperature in Kelvin (K). f L Temperature T C Equilibrium volume fraction of the liquid phase at (τ) M L : in mass% and temperature T C Equilibrium Mn concentration in the liquid phase at (τ) M δ : in mass% and temperature T C Equilibrium Mn concentration at δ under (τ) S L : in mass% and temperature T C Equilibrium Si concentration in the liquid phase at (τ) S δ : in mass% and temperature T C The equilibrium Si concentration at δ under (τ) D δ Mn : with m 2 Temperature T in seconds C The diffusion coefficient of Mn in the δ phase under (τ) D δ Si : with m 2 Temperature T in seconds C The diffusion coefficient of Si in the δ phase under (τ)
[10] The steel plate manufacturing method according to [8] or [9] may also include a plating process, in which a galvanized layer is formed on the surface of the hot-rolled steel plate or the surface of the cold-rolled steel plate during the first cooling process or the second cooling process of the heat treatment process, between the first cooling process or the second cooling process and the first holding process or the second holding process, during the first holding process or the second holding process, or after the first holding process or the second holding process.
[0030]
[11] According to the steel plate manufacturing method described in
[10] , the galvanized layer is a hot-dip galvanized layer, and the steel plate manufacturing method may further include an alloying process, in which the hot-dip galvanized layer is alloyed after the plating process to form an alloyed hot-dip galvanized layer.
[0031] Invention Effects According to the above-described manner of the present invention, a steel plate and a method for manufacturing the same can be provided, as well as a steel member obtained using the steel plate that can suppress fracture when subjected to axial crushing deformation, the steel plate having high strength and excellent elongation, and being able to suppress fracture of the member when subjected to axial crushing deformation after being formed into a member. Attached Figure Description
[0032] FIG. 1A It is a schematic diagram used to illustrate the implementation guidelines for axial crushing tests on components, and a diagram showing an example of the shape of a component with a closed cross-section structure.
[0033] FIG. 1B This is a schematic diagram illustrating the implementation guidelines for the axial crush test of a component, and it is a diagram showing an example of a welded part. Detailed Implementation
[0034] A steel plate according to one embodiment of the present invention (the steel plate of this embodiment), a steel component obtained using the steel plate (the steel component of this embodiment), and a method for manufacturing the same shall be described.
[0035] In this embodiment, the position where the thickness of the steel plate is 1 / 4 from the surface in the thickness direction is described as the 1 / 4 thickness position. Furthermore, in the case of a steel member, the position where the thickness of the steel member is 1 / 4 from the surface in the thickness direction (e.g., the thickness direction of the steel plate constituting the steel member) is described as the 1 / 4 thickness position.
[0036] <steel plate> The steel plate of this embodiment has a specified chemical composition. The microstructure at the 1 / 4 thickness position, by area percentage, comprises: retained austenite: 3-10%, ferrite: 0-10%, pearlite: 0-5%, and martensite and bainite: totaling 75-97%. In a cross-section parallel to the thickness direction, an 80μm × 80μm area centered at the 1 / 4 thickness position in the thickness direction and another 80μm area perpendicular to the thickness direction are divided into 16 20μm × 20μm portions. When calculating the area ratio of retained austenite in each portion, the standard deviation of the area ratio of retained austenite in each portion is set as σ1, and the average is set as γ. ave At that time, σ1 / γ ave It is below 0.20.
[0037] The steel plate in this embodiment can be a hot-rolled steel plate or a cold-rolled steel plate. In addition, an electro-galvanized layer, a hot-dip galvanized layer or an alloyed hot-dip galvanized layer can be formed on the surface (that is, it can be an electro-galvanized steel plate (EG), a hot-dip galvanized steel plate (GI), or an alloyed hot-dip galvanized steel plate (GA)).
[0038] In the case where the steel sheet has a coating (electroplated zinc coating, hot-dip galvanized coating, or alloyed hot-dip galvanized coating) (i.e., a coated steel sheet having a base material and a coating formed on the surface of the base material), the surface that serves as the reference at the 1 / 4 thickness position is the surface of the base material excluding the coating. Furthermore, the chemical composition of the steel sheet is also the chemical composition of the base material excluding the coating.
[0039] The following sections will explain each point.
[0040] (Chemical composition) The reasons for limiting the chemical composition of the steel plate in this embodiment will be explained. Unless otherwise specified, the "%" in the content of each element constituting the chemical composition refers to "mass %".
[0041] C: 0.08~0.20% Carbon (C) is an essential element for the formation of martensite and bainite, which contribute to the high strength of steel sheets. When the C content is below 0.08%, the desired microstructure cannot be obtained, and sufficient tensile strength cannot be achieved. Therefore, the C content is kept at 0.08% or higher. Preferably, the C content is 0.10% or higher.
[0042] On the other hand, if the carbon content exceeds 0.20%, the material's toughness decreases, and its fracture resistance during axial crushing deformation deteriorates. Furthermore, the weld metal becomes brittle, making it prone to fracture. Therefore, the carbon content is kept below 0.20%. Preferably, the carbon content is below 0.18%, more preferably below 0.15%.
[0043] That is, the C content is 0.08~0.20%, preferably 0.10~0.15%.
[0044] Si: 0.50~1.80% Silicon (Si) is a solid solution strengthening element and is effective in increasing the strength of steel sheets. Additionally, it increases the amount of retained austenite by suppressing the formation of iron carbides. To achieve this effect, the Si content is 0.50% or more. Preferably, the Si content is 0.80% or more.
[0045] On the other hand, if the Si content is excessive, the chemical conversion treatment properties and wettability of the steel sheet with hot-dip galvanization will be significantly deteriorated. Furthermore, the toughness of the material decreases, and its fracture resistance under axial crushing deformation deteriorates. Additionally, the weld fusion zone becomes embrittled, making it prone to fracture at the weld. Therefore, the Si content is kept to be 1.80% or less. The Si content is preferably 1.60% or less, and more preferably 1.40% or less.
[0046] That is, the Si content is 0.50~1.80%, preferably 0.80~1.40%.
[0047] Mn: 2.00~3.50% Manganese (Mn) is a strong austenite stabilizing element and an effective element for improving the hardenability of steel plates. To improve hardenability and increase the area ratio of martensite and bainite, the Mn content should be 2.00% or higher. Preferably, the Mn content is 2.20% or higher.
[0048] On the other hand, if the Mn content is excessive, the material's toughness decreases, and its fracture resistance during axial crushing deformation deteriorates. Furthermore, the weld metal becomes brittle, making it prone to fracture at the weld. Therefore, the Mn content is kept to be 3.50% or less. Preferably, the Mn content is 3.20% or less, more preferably 3.00% or less.
[0049] That is, the Mn content is 2.00~3.50%, preferably 2.20~3.00%.
[0050] P: below 0.050% Phosphorus (P) is a solid solution strengthening element and is effective in increasing the strength of steel plates. However, excessive P content deteriorates weldability and toughness. Therefore, the P content should be below 0.050%. Preferably, the P content is below 0.045%, 0.035%, or 0.020%. While the P content can be 0%, drastically reducing the P content would increase the cost of P removal; therefore, from an economic point of view, a lower limit of 0.001% is preferred.
[0051] S: Below 0.0100% Sulfur (S) is an element present as an impurity in steel, forming MnS and deteriorating its toughness and porosity. Therefore, the S content is kept below 0.0100%, which is considered a range where the deterioration of toughness and porosity is insignificant. The preferred S content is below 0.0050%, 0.0040%, or 0.0030%. While the S content can be 0%, drastically reducing the S content would increase desulfurization costs; therefore, from an economic point of view, a lower limit of 0.0001% is preferred.
[0052] Al: 0.001~1.000% Al (aluminum) must be present at least 0.001% for deoxidation of steel. The Al content can be 0.005% or more, 0.010% or more, or 0.020% or more. On the other hand, even with excessive Al content, the effect becomes saturated, leading not only to increased costs but also to higher phase transformation temperatures and increased loads during hot rolling, sometimes resulting in a decrease in the mechanical properties of the steel sheet. Therefore, the Al content is 1.000% or less. The Al content can be 0.800% or less, 0.600% or less, or 0.300% or less.
[0053] Ti: 0.001~0.100% Titanium (Ti) is an element that fixes dissolved nitrogen (N) in steel into TiN, thereby inhibiting the formation of boron (BN). To achieve this effect, the Ti content is 0.001% or more. Preferably, the Ti content is 0.005% or more.
[0054] On the other hand, if the Ti content is excessive, excessive Ti carbides will form, thus reducing toughness. Therefore, the Ti content is 0.100% or less. The Ti content is preferably set to 0.080% or less.
[0055] That is, the Ti content is 0.001~0.100%, preferably 0.005~0.080%.
[0056] B: 0.0005~0.0050% Boron (B) is an element that improves the hardenability of steel and reduces the area fraction of ferrite by segregating at austenite grain boundaries. To achieve this effect, the B content is set to 0.0005% or more. More preferably, the B content is 0.0008% or more.
[0057] On the other hand, if the boron content exceeds 0.0050%, the aforementioned effects are lost due to the formation of borides, and the hot workability decreases. Therefore, the boron content is 0.0050% or less. The boron content is preferably 0.0035% or less.
[0058] That is, the B content is 0.0005~0.0050%, preferably 0.0008~0.0035%.
[0059] N: below 0.0100% Nitrogen (N) is an element present as an impurity. If its content is high, it forms large nitrides in steel, sometimes deteriorating its flexibility and porosity. Therefore, the N content is limited to below 0.0100%. Preferably, the N content is below 0.0080%, 0.0060%, or 0.0050%. The N content can be 0%, but drastically reducing the N content would increase the cost of nitrogen removal; therefore, from an economic point of view, a lower limit of 0.0001% is preferred.
[0060] O: Below 0.0100% Oxygen (O) is an element present as an impurity. If its content is high, it forms coarse oxides in steel, sometimes deteriorating its flexibility and porosity. Therefore, the O content is limited to below 0.0100%. Preferably, the O content is below 0.0080%, 0.0060%, or 0.0050%. The O content can be 0%, but from a manufacturing cost perspective, a lower limit of 0.0001% is preferred.
[0061] The steel plate of this embodiment may contain the aforementioned elements, with the remainder being Fe and impurities. However, for the purpose of improving various properties, it may also contain one or more elements (arbitrary elements) selected from Cr, Mo, Cu, Ni, Co, W, Ta, Sn, Sb, Nb, V, As, Zn, Ca, Mg, Zr, Hf, Bi, and REM. Since arbitrary elements may not be present, the lower limit is 0%.
[0062] Cr: 0~1.00% Mo: 0~1.00% Cu: 0~1.00% Ni: 0~1.00% Co: 0~1.00% W: 0~1.00% Ta: 0~1.00% Sn: 0~1.00% Sb: 0~0.50% Nb: 0~0.200% V: 0~1.00% As: 0~0.10% Zn: 0~1.0000% Cr (chromium), Mo (molybdenum), Cu (copper), Ni (nickel), Co (cobalt), W (tungsten), Ta (tantalum), Sn (tin), Sb (antimony), Nb (niobium), V (vanadium), As (arsenic), and Zn (zinc) are all effective elements for increasing the strength of steel plates. One or more of these elements may be included as needed. The content of each element can be 0.001% or more, 0.005% or more, or 0.010% or more.
[0063] On the other hand, if these elements are excessively present, the effect will saturate, and the cost will increase. Therefore, when present, the contents of Cr, Mo, Cu, Ni, Co, W, Ta, Sn, and V are each 1.00% or less, the content of Zn is 1.0000% or less, the content of Sb is 0.50% or less, the content of Nb is 0.200% or less, and the content of As is 0.10% or less. The contents of Cr, Mo, Cu, Ni, Co, W, Ta, Sn, Sb, and V are preferably 0.40% or less, more preferably 0.30% or less, and even more preferably 0.20% or less. The content of Zn is preferably 0.4000% or less, more preferably 0.3000% or less, and even more preferably 0.20000% or less.
[0064] Ca: 0~0.0100% Mg: 0~0.0100% Zr: 0~0.0100% Bi: 0~0.0100% REM: 0~0.0100% Ca (calcium), Mg (magnesium), Zr (zirconium), and REM (rare earth elements) are elements that help to finely disperse inclusions in steel, while Bi (bismuth) is an element that reduces the microscopic segregation of substitutional alloying elements such as Mn and Si in steel. These elements respectively contribute to improving the flexibility of steel plates. Therefore, they can be included as needed.
[0065] To achieve the above-mentioned effects, it is preferable to contain 0.0001% or more of one or more selected from Ca, Mg, Bi, Zr and REM, and more preferably 0.0010% or more.
[0066] On the other hand, excessive content of these elements will degrade the elongation. Therefore, the contents of Ca, Mg, Bi, Zr, and REM are all 0.0100% or less. Preferably, the contents of Ca, Mg, Bi, Zr, and REM are all 0.0080% or less, more preferably 0.0060% or less.
[0067] Here, REM refers to the 17 elements including Sc, Y, and the lanthanides, and REM content refers to the total content of these elements. In industry, the lanthanides are added as a mixture of rare earth metals.
[0068] Hf: 0~0.0100% Hf is effective as a deoxygenating element. Therefore, it can also be present.
[0069] On the other hand, if the Hf content exceeds 0.0100%, the toughness of the HAZ deteriorates, therefore the Hf content is 0.0100% or less. The Hf content is preferably 0.0080% or less, and more preferably 0.0050% or less.
[0070] As described above, the steel plate of this embodiment may contain C, Si, Mn, P, S, Al, Ti, B, N, and O, with the remainder being Fe and impurities. It may also contain one or more elements (any element). Impurities refer to components that are mixed in from raw materials such as ore and waste or due to other factors during the industrial manufacturing of steel, and are permissible within a range that does not adversely affect the properties.
[0071] The chemical composition of the steel plate in this embodiment can be determined using conventional methods. For example, according to JIS G 1201:2014, the chemical composition can be determined using ICP-AES (Inductively Coupled Plasma-Atomic Emission Spectrometry). In this case, the chemical composition is the average content of the total plate thickness. C and S, which are difficult to determine in ICP-AES, can be determined using the combustion-infrared absorption method, N can be determined using the inert gas melting-thermal conductivity method, and O can be determined using the inert gas melting-non-dispersive infrared absorption method.
[0072] The analytical samples were collected in a manner as described in JIS G 0417:1999, in order to obtain the average chemical composition of the steel plate throughout its thickness. Specifically, the analytical samples were collected from a position one-quarter of the thickness, avoiding the ends in the width direction of the steel plate.
[0073] In the steel plate of this embodiment, based on setting the average Mn content and Si content in the steel plate as within the ranges mentioned above, the standard deviation σ (σ2 in this embodiment) of the MS value calculated by formula (1) for the mass percentage concentrations [Mn] and [Si] of Mn and Si at each of the multiple measurement points measured by EPMA is preferably 0.80 or less.
[0074] MS=[Mn]+(2 / 3)×[Si]…(1) If the standard deviation σ2 of the MS value is small, then the fracture of the HAZ section is suppressed when the component with spot welds is subjected to axial crushing deformation after molding.
[0075] The reason why it is speculated that if the standard deviation σ2 of the MS value is large, fracture is more likely to occur is as follows.
[0076] During welding, the HAZ (Heat Zone) heats up due to the welding heat. Within the HAZ, there exists a region reaching a two-phase temperature (Ac1~Ac3). Furthermore, the cooling rate of the welded area is extremely high, causing the austenite formed to become quenched martensite. That is, in this region, the microstructure becomes a composite structure containing ferrite and martensite. Such a structure is brittle, making it prone to fracture under axial crushing deformation. In particular, the higher the proportion of martensite containing large amounts of Si and Mn, the more brittle it becomes. The smaller the standard deviation σ2 of the MS value of the steel plate, the smaller the proportion of such Si and Mn martensite in the HAZ, thus fracture is considered to be suppressed.
[0077] The standard deviation of the MS value is determined by the following method.
[0078] The concentration distribution of Si and Mn was measured using a FE-EPMA (electron probe microanalyzer). In a section parallel to the plate thickness direction, within a 35 μm × 50 μm region centered at the 1 / 4 thickness position and extending from the surface of the steel plate towards the thickness direction (range from 1 / 8 to 3 / 8 thickness position), the Si and Mn concentrations were measured at intervals of 0.2 μm. The concentration of [Mn] + (2 / 3) × [Si] was calculated from the Mn concentration [Mn] and Si concentration [Si] at each measurement position. Through the above analysis across four fields of view, the value of [Mn] + (2 / 3) × [Si] was obtained at approximately 175,000 points. This value was used as the overall calculated standard deviation σ (σ²).
[0079] For FE-EPMA, such as the JEOL JXA-8530F, the accelerating voltage can be 15kV. The characteristic X-rays are dispersed using a wavelength-dispersive method. The appropriate spectroscopic crystal is selected based on the element being analyzed; for example, LiF is used for Mn, and TAP is used for Si. The output Si and Mn concentrations are converted from the characteristic X-ray detection intensity to a mass percentage value using a program attached to the JXA-8530, provided that calibration based on standard materials has been performed.
[0080] (Micro-organization) [1 / 4 thickness position] In the steel sheet of this embodiment, the microstructure (metallic structure) at a position where the sheet thickness is 1 / 4 from the surface in the thickness direction has the following structure (phase). Hereinafter, the proportions of each structure are area ratios.
[0081] Residual austenite: 3~10% Retained austenite is a microstructure that contributes to increased elongation through the TRIP effect. Therefore, the area fraction of retained austenite is over 3%.
[0082] On the other hand, if the area ratio of retained austenite is excessive, the grain size of the retained austenite becomes larger. Such large-grained retained austenite becomes coarse and hard martensite after deformation such as forming. In this case, it is easy to generate the initiation point of cracks, and the flexibility deteriorates. Therefore, the area ratio of retained austenite should be less than 10%.
[0083] Ferrite: 0~10% To suppress fracture during axial crushing deformation after component forming, a uniform microstructure with small hardness differences between microstructures is preferred. Ferrite is a soft microstructure (phase), therefore, if the microstructure becomes dominated by ferrite, it is difficult to obtain high strength.
[0084] Therefore, in the steel sheet of this embodiment, the microstructure is mainly composed of martensite and bainite as described later. Therefore, the ferrite area fraction is 10% or less. A lower ferrite area fraction is better, preferably 5% or less, more preferably 3% or less, and can also be 0%.
[0085] Pearlite: 0~5% Pearlite is a brittle structure and becomes the starting point for failure, thus deteriorating the local ductility of the steel sheet. Therefore, its area fraction is set to 5% or less. The area fraction of pearlite is preferably 3% or less, more preferably 2% or less, and can also be 0%.
[0086] Martensite and bainite: totaling 75-97%. Martensite and bainite are effective microstructures for increasing the strength of steel sheets. As mentioned above, in order to suppress fracture during axial crushing deformation after the component is formed, it is necessary to form a microstructure that is as uniform as possible. Therefore, in the steel sheet of this embodiment, in addition to retained austenite, ferrite, and pearlite, there is martensite and / or bainite.
[0087] The combined area ratio of martensite and bainite is 75-97%. Preferably, the combined area ratio of martensite and bainite is 80-97%, specifically 85-97% or 90-97%.
[0088] Both martensite and bainite are lath-like structures, and in the steel sheet of this embodiment, their respective area ratios do not need to be specifically specified (one can even be 0%). Here, martensite includes so-called primary martensite and tempered martensite.
[0089] The area fraction of each phase in the microstructure (metallic structure) at 1 / 4 thickness position of the steel plate in this embodiment was measured as follows.
[0090] The area ratio of the tissue was evaluated using secondary electron microscopy (FE-SEM) and X-ray diffraction. For example, a JEOL JSM-7200F FE-SEM can be used. First, a sample was taken from a section parallel to the rolling direction of the steel plate (a section parallel to the thickness direction) at least 50 mm from the end in the width direction, using this section as the observation surface. The observation surface was mechanically ground to a mirror finish and then etched using a nitric acid-ethanol solution. Next, in one or more observation fields centered on a position 1 / 8 to 3 / 8 of the thickness from the surface of the steel plate, a total of 2.0 × 10⁻⁶ X-rays were used. -9 m 2Secondary electron images were taken of the area shown above. The area fractions of ferrite and pearlite were measured from the obtained secondary electron images, and these were taken as the area ratio. The upper limit of the field of view does not need to be determined, but the larger the area, the greater the time required for point counting; therefore, a value of 1.0 × 10⁻⁶ was used. -8 m 2 The following can be used as a baseline. The magnification is set to 5000x, and the field of view is 2.0 × 10⁻⁶. -9 m 2 The above number of sheets.
[0091] During microstructure identification, areas where cementite precipitates in a lamellar pattern are identified as pearlite. Additionally, areas with low brightness and where the underlying microstructure is not identified are identified as ferrite. Areas not meeting any of these criteria are identified as bainite, martensite, or austenite (retained austenite). The area ratios of bainite and martensite can be calculated by subtracting the area ratio of austenite determined by X-ray diffraction (described later) from the area ratio of the areas identified as bainite, martensite, or austenite. The area ratios of each microstructure are then calculated using a point counting method. The point counting intervals are 2 μm both horizontally and vertically.
[0092] The area fraction of retained austenite was determined by X-ray diffraction. Specifically, the steel plate was removed from its thickness direction to a depth of 1 / 4 by mechanical and chemical grinding. Then, the microstructure fraction of retained austenite was calculated based on the integral intensity ratio of the diffraction peaks of the (200), (211) phase of the bcc phase and the (200), (220), (311) phase of the fcc phase obtained by using the MoKα1 line as the characteristic X-ray, and this ratio was taken as the volume fraction of retained austenite. In the steel plate of this embodiment, the volume fraction and area fraction were considered equal, and the obtained volume fraction of retained austenite was set as the area fraction of retained austenite.
[0093] The rolling direction is obvious when the raw material is coil and the rolling direction is recorded. In the case of a full-width cut plate sample, if the width is known, the rolling direction can be determined based on the dimensions. Furthermore, if at least one side of the width edge remains, those skilled in the art can easily determine the width direction and rolling direction based on the end face condition (whether there is edge thinning, whether there is plating). In the case of lost information, the rolling direction is determined by the following method: The Z-side of the plate (the surface parallel to both the length and width directions of the plate) is ground to 1 / 4 thickness, and after mirror polishing, a 1000 μm × 1000 μm Mn concentration mapping is obtained in EPMA. When Mn solidification segregation is measured in a striped pattern, the length direction of the stripe pattern is determined as the rolling direction. Furthermore, even when the steel plate is processed into a component, the above method can be used to determine the rolling direction for weakly machined portions of the component (e.g., flat portions not subjected to comparative machining).
[0094] In the steel plate of this embodiment, in a cross-section parallel to the plate thickness direction, an 80μm × 80μm area centered at 1 / 4 of the plate thickness in the thickness direction and 80μm in a direction perpendicular to the plate thickness direction is divided into 16 20μm × 20μm portions. When calculating the area ratio of retained austenite in each divided region, the standard deviation of the area ratio of retained austenite in each divided region is set as σ1, and the average is set as γ. ave At that time, σ1 / γ ave It is below 0.20.
[0095] Retained austenite transforms into hard martensite through work-induced phase transformation, thereby contributing to increased work hardening. σ1 / γ ave A larger value means a greater deviation in the distribution of retained austenite. Such a microstructure, when subjected to processing based on axial crushing deformation, exhibits uneven work hardening based on processing-induced phase transformation, resulting in uneven hardness between microstructures and thus susceptibility to fracture during axial crushing deformation. Therefore, reducing σ1 / γ... ave Set it to below 0.20. σ1 / γ ave Preferably, it is 0.15 or less, and more preferably 0.10 or less.
[0096] σ1 / γ ave The following methods were used to determine this.
[0097] First, a sample is collected from a section of the steel plate at least 50 mm from the end in the width direction, using the plate thickness section as the observation surface. This section is preferably parallel to the rolling direction. The observation surface is mechanically ground to a mirror finish, followed by electrolytic grinding. Next, for the plate thickness direction in the observation surface, the crystal structure and orientation of an 80 μm × 80 μm area centered at 1 / 4 of the plate thickness and extending perpendicularly to the plate thickness direction is analyzed using SEM-EBSD. For example, a JEOL JSM-7200F FE-SEM can be used. For the analysis of data obtained by the EBSD method, for example, TSL's "OIM Analysis 6.0" can be used. The evaluation point spacing (step) is 0.1 μm. Regions with an FCC crystal structure are considered retained austenite. The resulting 80 μm × 80 μm area is divided into 16 20 μm × 20 μm sections, and the area fraction of retained austenite in each section is measured. For the 16 specimens obtained in this way, calculate the standard deviation σ1 and the mean γ. ave Calculate σ1 / γ ave .
[0098] (Mechanical properties) The steel sheet in this embodiment aims for a tensile strength (TS) of 980 MPa or higher, which contributes to the lightweighting of the automobile body. While there is no upper limit to the tensile strength, higher tensile strength may reduce formability; therefore, a tensile strength of 2000 MPa or lower can also be set. Furthermore, an elongation (EL) of 10.0% or higher is targeted.
[0099] Tensile strength (TS) and elongation (EL) are determined by taking a JIS 5 tensile test piece from the steel sheet in a direction perpendicular to the rolling direction and performing a tensile test according to JIS Z 2241:2022. If the rolling direction is difficult to determine, the tensile test can be performed in any direction. Alternatively, if it is difficult to take a JIS 5 tensile test piece, a JIS 13B tensile test piece can be used. If that is also difficult, any small test piece with a similar shape to the JIS 13B tensile test piece can be used. In this case, the distance between the markings can be changed according to the scale of the test piece; for example, if a 1 / 2 similar shape is used, the distance between the markings can be set to 25 mm.
[0100] (plate thickness) The thickness of the steel plate in this embodiment is not limited, but from the viewpoint of balancing the lightweighting of the automobile body and the suppression of fracture during crushing deformation as a component, it is preferably 0.4 to 3.0 mm.
[0101] (Zinc plating) (Alloyed hot-dip galvanized layer) The steel sheet in this embodiment may have a galvanized layer on its surface (or it may have a base steel sheet and a galvanized layer formed on the surface of the base steel sheet). The galvanized layer improves corrosion resistance. For automotive steel sheets, even with high strength, it is sometimes impossible to reduce the sheet thickness to below a constant thickness if there are concerns about corrosion causing porosity. One purpose of increasing the strength of steel sheets is to achieve weight reduction through thinning; therefore, even if high-strength steel sheets are developed, their application is limited if their corrosion resistance is low. As a solution to these problems, a highly corrosion-resistant galvanized layer can be formed on the surface of the steel sheet.
[0102] The galvanized layer can be an electroplated galvanized layer, a hot-dip galvanized layer, or an alloyed hot-dip galvanized layer. Hot-dip galvanized layers are preferred in terms of cost. In alloyed hot-dip galvanized layers, Fe is introduced into the galvanized layer through alloying treatment, thus resulting in excellent weldability and paintability, making it a preferred option.
[0103] In addition, to improve paintability and weldability, an upper coating can be applied to the galvanized layer (electroplated galvanized layer, hot-dip galvanized layer, alloyed hot-dip galvanized layer). Furthermore, in the cold-rolled steel sheet of this embodiment, various treatments can be applied to the hot-dip galvanized layer, such as chromate treatment, phosphate treatment, lubricity improvement treatment, weldability improvement treatment, etc.
[0104] The galvanized layer and alloyed hot-dip galvanized layer can contain Zn and Fe, but in addition to Zn and Fe, they can also contain elements such as Al, Mg, and Si. Furthermore, there are no particular restrictions on the amount of galvanized layer applied; it can be a typical application rate. For automotive applications, a typical application rate is, for example, 20~100 g / m² per side. 2 .
[0105] <Steel Components> The steel component in this embodiment is a steel component obtained by forming the steel plate of this embodiment into a specified shape, or a steel component obtained by further joining it with other steel materials by spot welding after forming.
[0106] A steel component obtained by forming (processing) into a specified shape has a steel plate containing both processed and unprocessed parts.
[0107] In addition, the steel component obtained by spot welding with other steel materials has a steel plate, which includes a spot weld portion, a HAZ portion formed around the spot weld portion and affected by the heat of the spot weld, the spot weld portion, and a non-welded portion other than the HAZ portion.
[0108] Here, the unmachined portion is the flat part of a steel structure, and it is the thickest part among the flat parts. In a steel structure, the machined portion is the part of the flat part that is thinner than the surrounding area or has a constant curvature.
[0109] In addition, the non-welded part is the part other than the HAZ part which is affected by the heat of the spot weld and the spot weld.
[0110] The steel component comprises the aforementioned steel plate. Alternatively, the steel component may also comprise the aforementioned steel plate. Furthermore, the surface of the steel plate constituting the steel component may have a hot-dip galvanized layer or an alloyed hot-dip galvanized layer.
[0111] The steel component (before spot welding) in this embodiment has the following characteristics in the non-machined part.
[0112] If the steel component is an automotive part, it can be exemplified as being applicable to front side beams, rear side beams, side beams, etc.
[0113] The steel component (before spot welding) in this embodiment has the following characteristics in the non-machined part.
[0114] In addition, the steel component (after spot welding) of this embodiment has the following characteristics in the non-machined part of the non-welded part.
[0115] (Non-machined and non-welded parts (if it is a steel component before spot welding, then it is a non-machined part)) The non-welded portions are not affected by spot welding, therefore their chemical composition is the same as that of the steel sheet of this embodiment. Furthermore, while the microstructure changes through forming processes, the non-machined portions, where processing strain does not enter, are the same as those of the steel sheet of this embodiment.
[0116] That is, in the non-processed and non-welded parts, there are components, by mass%, including C: 0.08~0.20%, Si: 0.50~1.80%, Mn: 2.00~3.50%, P: less than 0.050%, S: less than 0.0100%, Al: 0.001~1.000%, Ti: 0.001~0.100%, B: 0.0005~0.0050%, N: less than 0.0100%, O: less than 0.0100%, Cr: 0~1.00%, Mo: 0~1.00%, Cu: 0~1.00%, Ni: 0~1. Chemical composition of Fe and impurities.
[0117] Furthermore, in the non-processed and non-welded sections, the microstructure at the 1 / 4 thickness position (e.g., the thickness of the steel plate constituting the component) from the surface in the thickness direction comprises, by area percentage: retained austenite: 3-10%, ferrite: 0-10%, pearlite: 0-5%, and martensite and bainite: totaling 75-97%. In a section parallel to the thickness direction, an 80μm × 80μm area centered at the 1 / 4 thickness position in the thickness direction and another 80μm area perpendicular to the thickness direction is divided into 16 20μm × 20μm portions. When calculating the area ratio of retained austenite in each segmented region, the standard deviation of the area ratio of retained austenite in each segmented region is set as σ1, and the average is set as γ. ave At that time, σ1 / γ ave It is below 0.20.
[0118] With such a chemical composition and microstructure, fracture during axial crushing deformation can be suppressed.
[0119] The chemical composition of the non-processed and non-welded parts does not change significantly from the steel plate of this embodiment. Therefore, the standard deviation σ2 of the mass percentage concentrations [Mn] and [Si] of Mn and Si, calculated by Equation (1), at each of the multiple measurement points measured by EPMA in the 35μm×50μm region of the cross section in the thickness direction (in the case of the steel plate, the plate thickness direction of the steel plate) centered at the 1 / 4 thickness position, can be 0.80 or less.
[0120] MS=[Mn]+(2 / 3)×[Si]…(1) In non-machined and non-welded sections, if the standard deviation of the MS value σ (σ2) is less than or equal to 0.80, the fracture of the HAZ section is suppressed when subjected to axial crushing deformation after spot welding.
[0121] Furthermore, in steel components with spot welds, if the standard deviation σ2 of the MS value at non-machined and non-welded parts is less than 0.80, then the fracture of the HAZ section is suppressed when subjected to axial crushing deformation.
[0122] Furthermore, the mechanical properties and thickness can also be the same as those of the steel plate in this embodiment.
[0123] The other steel plates joined by spot welding may be the steel plates of this embodiment or not. If the other steel plates are not the steel plates of this embodiment, the portion obtained from the steel plates of this embodiment only needs to satisfy the above description. That is, a portion of the steel component only needs to satisfy the above description.
[0124] (Spot welding section) There are no restrictions on the spot weld. Any spot weld formed under normal welding conditions is acceptable.
[0125] Chemical composition, microstructure, and σ1 / γ of non-machined and non-welded parts ave The standard deviations of the concentration distributions of Mn and Si can be determined using the same methods as for steel plates. Regarding mechanical properties, as long as JIS 5 tensile test specimens can be taken from the non-machined and non-welded parts of the component, the results can be determined using the same methods as for steel plates. However, if JIS 5 tensile test specimens cannot be taken, the tensile strength of JIS 13B tensile test specimens or small test specimens of similar shape to JIS 13B tensile test specimens can be evaluated as described above.
[0126] <Manufacturing Method> The steel plate and steel components of this embodiment are independent of the manufacturing method; as long as they possess the aforementioned characteristics, their effects can be achieved. However, the following method allows for stable manufacturing and is therefore preferred.
[0127] The steel plate of this embodiment is obtained by a manufacturing method including the following steps (I) to (IV).
[0128] (I) A continuous casting process for obtaining slabs with a specified chemical composition by continuous casting.
[0129] (II) The slab is heated to a heating temperature and hot-rolled, including rough rolling and finish rolling. After cooling to a coiling temperature, it is coiled at the coiling temperature to obtain a hot-rolled steel plate.
[0130] (III) A cold rolling process, as needed, pickling the hot-rolled steel sheet and cold rolling it with a cumulative reduction rate of 30-75% to obtain a cold-rolled steel sheet.
[0131] (IV) A heat treatment process for heat-treating the hot-rolled steel sheet or the cold-rolled steel sheet.
[0132] Furthermore, in the steel plate manufacturing method of this embodiment, when cold rolling is performed, one or both of the following processes can be performed arbitrarily between the hot rolling process and the cold rolling process.
[0133] (II') Pickling process for pickling the hot-rolled steel sheet.
[0134] (II) The hot-rolled steel plate heat treatment process for heat treatment of the hot-rolled steel plate.
[0135] When the steel plate of this embodiment is a plated steel plate, one or both of the following processes can be further performed on the steel plate (hot-rolled steel plate or cold-rolled steel plate) obtained in the above process.
[0136] (V) A coating process that forms a zinc coating on the surface of a steel plate.
[0137] (VI) The hot-dip galvanized layer is used as an alloying process for the alloyed hot-dip galvanized layer.
[0138] In addition, the steel component of this embodiment is obtained by further supplying the steel plate (hot-rolled steel plate or cold-rolled steel plate) obtained by (I) to (IV) above, or the steel plate (galvanized steel plate) obtained by (I) to (V) or (I) to (VI) below to the following process (VII), or (VII) and (VIII).
[0139] (VII) A forming process for forming the steel plate of this embodiment into a specified shape.
[0140] (VIII) A joining process in which the steel plate after the forming process is joined with other steel plates by spot welding.
[0141] The optimal conditions for each process are explained.
[0142] (Continuous casting process) In the continuous casting process, a slab with the same chemical composition as the steel plate of this embodiment is obtained by continuous casting.
[0143] In the steel plate obtained after the subsequent processes, if the standard deviation σ of the MS value calculated by Equation (1) based on the concentration of Mn [Mn] and the concentration of Si [Si] is set to 0.80 or less, in the continuous casting process, it is preferable to cast in a manner that satisfies Equation (4).
[0144] Here, T in equation (4) C (τ) is obtained from equation (5).
[0145] [Mathematical Expression 5] [Mathematical Expression 6] Here, τ, τ1, and T in equations (4) and (5) above. S (τ), T C (τ), T L f L M L M δ S L S δ D δ Mn D δ Si The following are respectively represented.
[0146] τ: Elapsed time [seconds] since casting began τ1:T C (τ) The solidification end temperature T at unit K. δ Time (seconds) T S (τ): Slab surface temperature [K] at time τ T C (τ): Estimated internal temperature (center temperature) of the slab over time τ [K] T L Solidification onset temperature [K] f L Temperature T C Equilibrium volume fraction of the liquid phase at (τ) M L Temperature T C Equilibrium Mn concentration [mass%] in the liquid phase at (τ) M δ Temperature T C(τ) Equilibrium Mn concentration [mass%] at δ S L Temperature T C Equilibrium Si concentration [mass%] in the liquid phase at (τ) S δ Temperature T C (τ) Equilibrium Si concentration [mass%] at δ D δ Mn Temperature T C The diffusion coefficient of Mn in the δ phase under (τ) [m 2 / Second] D δ Si Temperature T C The diffusion coefficient of Si in the δ phase under (τ) [m] 2 / Second] In the case of continuous casting of slabs from molten steel, the molten steel is initially liquid but gradually solidifies from the surface, completely solidifying at a certain temperature (i.e., the solidification end temperature). Relatedly, Equation (4) defines the temperature region where the liquid and solid phases coexist before the molten steel completely solidifies (the temperature region under partial solidification). In this temperature region, as solidification proceeds from the surface of the molten steel, alloying elements are distributed (displaced) from the solid phase to the liquid phase, thus enriching the alloying elements in the liquid phase during this stage. This enrichment of alloying elements is the main reason for the increase in the standard deviation σ of the MS value. More specifically, the greater the distribution of Mn and Si between the solid and liquid phases, the more regions with higher / lower MS values are locally generated in the final product. Therefore, it is important to sufficiently suppress the distribution of Mn and Si between the solid and liquid phases in the temperature region where the liquid and solid phases coexist during continuous casting. In this regard, the inventors have discovered that by satisfying equations (4) and (5), especially by controlling the value obtained from the left side of equation (4) to be less than 0.0100, the distribution of Mn and Si between the solid and liquid phases can be suppressed, and the standard deviation σ of the MS value can be significantly reduced.
[0147] Here, τ=0 in equation (4) means the start of casting, and τ1 means the internal temperature (center temperature) of the slab reaches the solidification completion temperature T. δ The time (seconds). Therefore, equation (4) can be understood as integrating the distribution of Mn from the solid phase to the liquid phase over time. Therefore, the smaller the value on the left side of equation (4), the more the distribution of Mn and Si from the solid phase to the liquid phase is suppressed. The smaller the value on the left side of equation (4), the better, specifically, preferably 0.0100 or less, more preferably 0.0050 or less, or 0.0030 or less. T in equations (4) and (5) L T S f L M L Mδ S L S δ D δ Mn D δ Si It is a value determined by temperature and the chemical composition of the molten steel. T C (τ) is the internal temperature (center temperature) of the slab at time τ, which is estimated from the surface temperature of the slab using equation (5). The surface temperature of the slab is measured at 1-second intervals. In cases where it is difficult to measure the surface temperature at 1-second intervals, the value at a 1-second interval can be obtained by linear interpolation between the measurement points. In cases where the measurement interval is less than 1 second, the data can be rounded to a 1-second interval by dividing the interval. Therefore, those skilled in the art can control the value calculated on the left side of equation (4) within the desired range by appropriately selecting the chemical composition of the molten steel and the temperature history during continuous casting.
[0148] T L T δ f L M L M δ S L S δ For example, the composition of the steel can be determined by performing a state diagram calculation using the commercially available thermodynamic calculation software "Thermo-Calc2022b" (Thermo-Calc Software Inc.). Let the phases being calculated be the LIQUID phase and the BCC_A2 phase, with other phases represented as SUSPEND. Equilibrium calculations are performed in one-axis mode, with temperature as the variable. The calculation temperature range only needs to include the temperature range where the LIQUID phase has a molar number of 0 to 1, for example, 1400 to 1600 °C. The step division number is set to 1 °C per calculation result. For example, if the calculation temperature range is 200 °C, then 200 divisions are used. The step method is set to Normal. The pressure is set to 100,000 Pa, the system size is 1 mol, and Globalminimization is enabled. After the calculation, the Mn and Si concentrations in the LIQUID phase and the Mn and Si concentrations in the BCC_A2 phase are used as temperature variables, and the output values are set as the Mn concentrations at each temperature. L S L M δ S δ The volumes of the LIQUID and BCC_A2 phases are output as temperature variables. The volume of the LIQUID phase is divided by the sum of the volumes of the LIQUID and BCC_A2 phases, and the resulting value is taken as f at each temperature. L Output the Mol number of the LIQUID phase, and set the lowest temperature at which the Mol number becomes 1 as T.L Let T be the highest temperature at which the Mol number becomes 0. δ Additionally, D δ Mn D δ Si Use the values obtained by the following equations (6) and (7).
[0149] [Mathematical Expression 7] [Mathematical Expression 8] (Hot rolling process) In the hot rolling process, the slab is heated to the heating temperature and hot rolling including rough rolling and finish rolling is carried out. After cooling to the coiling temperature, it is coiled at the coiling temperature to obtain hot-rolled steel plate.
[0150] In the hot rolling process, the heating temperature of the slab is set to above 1200°C. Below 1200°C, the diffusion of alloying elements is insufficient. There is no upper limit to the heating temperature, but to suppress the decrease in yield caused by oxide scale peeling, it is preferably below 1350°C.
[0151] Furthermore, to ensure a uniform distribution of retained austenite in the final microstructure, when the number of finish rolling passes is set to n, the initial pass is set to pass 1, and the final pass is set to pass n, the inlet temperature of pass n-2 (i.e., the third pass from the final number) is set to 950°C or higher, and the outlet temperature (surface temperature of the steel plate) of pass n (the final pass) is set to 900°C or higher. In finish rolling, at least one reduction exceeding 25% in a single pass is performed. Additionally, the time between each pass (n-2 and n-1, and between n-1 and n) is set to 0.2 to 1.0 seconds, and the time from the end of pass n to the start of cooling is set to 1.0 to 3.0 seconds. There is no upper limit to the inlet and outlet temperatures; both can be below 1100°C.
[0152] As a result, the number of nucleation sites for phase transformation increases, thus refining the microstructure of the hot-rolled plate and uniformly dispersing the cementite, which becomes the source of retained austenite.
[0153] If more than one of the following is outside the range: the inlet temperature of the (n-2)th pass (i.e., the outlet temperature of the nth pass), the number of reductions exceeding 25% in a single pass, the time between the final three passes, and the time from the end of the final pass to the start of cooling, then the cementite is not sufficiently uniformly dispersed. If the cementite is non-uniformly distributed, the distribution of carbon (C) in the austenite becomes uneven during heating in the subsequent heat treatment process, resulting in locally generated austenite regions with low C concentrations. From such austenite phase transformation into martensite or bainite, the C concentration decreases, and the distribution of retained austenite in the final microstructure becomes uneven.
[0154] In processes following the hot rolling process, unless otherwise specified, the temperature managed is the surface temperature of the steel plate.
[0155] In addition, during the cooling process after the final pass (nth pass), the temperature is cooled to a winding temperature of 200-550°C with an average cooling rate of 20°C / s or more between 600-750°C.
[0156] This results in a microstructure dominated by martensite and bainite, ensuring uniform dispersion of cementite. When the average cooling rate between 600 and 750°C is less than 20°C / s, or the coiling temperature exceeds 550°C, a large amount of non-martensite and non-bainite microstructures such as ferrite and pearlite are formed, and cementite is not uniformly dispersed. The preferred coiling temperature is below 540°C.
[0157] Furthermore, when the coiling temperature is below 200°C, uneven cooling can cause the hot-rolled strip coil to break down, potentially hindering productivity. There is no specific upper limit to the average cooling rate between 600 and 750°C; from an operational standpoint, it can be below 200°C / s.
[0158] Furthermore, in the steel sheet obtained after subsequent processes, with the standard deviation σ² of the MS value set to 0.80 or less, during rough rolling, it is preferable to perform at least three rolling passes with a reduction rate exceeding 20% at a steel sheet temperature of 1050°C or higher. There is no upper limit to the number of rolling passes exceeding 20%, which can be set to seven or less. There is no particular upper limit to the rough rolling temperature; from an operational point of view, it can be set to 1250°C or lower.
[0159] (Pickling process) In the pickling process, hot-rolled steel sheets are pickled. The pickling method can follow conventional methods. Alternatively, a pickling process can be omitted. Furthermore, to correct the shape of the hot-rolled strip and improve its pickling properties, leveling rolling can also be performed.
[0160] (Heat treatment process for hot-rolled steel plates) To reduce the load on the cold rolling mill, a heat treatment to soften the hot-rolled sheet can be performed before cold rolling. When performing heat treatment, if the maximum reaching temperature is below 400°C, softening may not be sufficient. Furthermore, above 650°C, cementite coarsens, delaying the reverse phase transformation during the heat treatment process, sometimes resulting in an undesirable microstructure. Therefore, the maximum reaching temperature is preferably 400–650°C. The residence time can be approximately 60 seconds to 40 hours. This heat treatment can be performed before or after pickling.
[0161] (Cold rolling process) In the cold rolling process, hot-rolled steel sheets are pickled and then cold-rolled with a cumulative reduction rate of 30-75% to obtain cold-rolled steel sheets. However, the cold rolling process can be omitted. When the reduction rate is higher than 75%, the load on the equipment increases unnecessarily, leading to a unnecessary increase in costs. On the other hand, when the reduction rate is lower than 30%, the roughness of the rolling rolls is not fully transferred to the surface of the steel sheet, resulting in a worse surface roughness compared to when the reduction rate is higher than 30%.
[0162] (Heat treatment process) In the heat treatment process, hot-rolled steel sheets (without cold rolling) or cold-rolled steel sheets (with cold rolling) (sometimes collectively referred to as steel sheets) are subjected to heat treatment.
[0163] The heat treatment process includes a heating process, a first cooling process, a first holding process, a second cooling process, and a second holding process. Through heat treatment, the microstructure can be controlled.
[0164] (Heating process) During the heating process, hot-rolled or cold-rolled steel sheets are heated to a temperature range of Ac3-20℃ to 950℃ and held in this temperature range for 1 to 1000 seconds.
[0165] When the heating temperature (maximum heating temperature) is below Ac3-20℃ or the holding time is less than 1 second, sufficient austenitic phase transformation will not occur, and the specified microstructure will not be obtained in the steel sheet after the final process.
[0166] On the other hand, when the heating temperature exceeds 950°C or the holding time exceeds 1000 seconds, the austenite grain size increases excessively, resulting in reduced toughness.
[0167] (First cooling process) (First retention process) In the first cooling process, the hot-rolled or cold-rolled steel sheet after the heating process is cooled to the first cooling stop temperature at an average cooling rate of 10°C / s or more between 650°C and 550°C. At this time, the first cooling stop temperature is within the range of Ms-50°C to 550°C (the first temperature range).
[0168] Then, during the first holding process, the hot-rolled or cold-rolled steel sheet after the first cooling process is held in the first temperature range for 20 to 100 seconds. During this process, the steel sheet only needs to be held in the temperature range of Ms-50℃ to 550℃ for 20 to 100 seconds, and it is not necessary to maintain a constant temperature.
[0169] By maintaining the first temperature region, a partial bainitic phase transformation occurs, forming a C-rich region. This C-rich region contributes to the homogenization of the distribution of retained austenite.
[0170] If the average cooling rate between 650 and 550°C during the first cooling process is less than 10°C / s, a large amount of ferrite will be generated during cooling, making it impossible to obtain the specified microstructure. There is no specific upper limit; from an operational point of view, it can be below 200°C / s.
[0171] Furthermore, if the cooling stop temperature is lower than Ms-50°C (which is lower than the first temperature range), the martensite will be tempered in subsequent plating processes, resulting in an uneven distribution of retained austenite. On the other hand, if the cooling stop temperature exceeds 550°C, ferrite will form, making it difficult to obtain the desired microstructure.
[0172] Furthermore, when the holding time in the first temperature region (the time the steel plate remains in the temperature region of Ms-50℃ to 550℃) is less than 20 seconds, the effect of partially carrying out the bainitic phase transformation is insufficient, and the distribution of retained austenite becomes uneven. On the other hand, if the holding time exceeds 100 seconds, the bainitic phase transformation proceeds excessively, resulting in an uneven distribution of retained austenite.
[0173] Here, Ac3 and Ms (phase transition point) (°C) can be obtained by the following formula.
[0174] Ac3=912-230.5×[C]+31.6×[Si]-20.4×[Mn]-39.8×[Cu]-18.1×[Ni]-14.8×[Cr]+16.8×[Mo]+100×[Al] Ms=561-474×[C]-33×[Mn]-17×[Cr]-17×[Ni]-21×[Mo]-7.5×[Si]+10×[Co] In the formula, [element] represents the mass percentage of each element in the steel plate.
[0175] (Second cooling process) (Second retention process) In the second cooling process, the hot-rolled or cold-rolled steel sheet after the first holding process is cooled to below 200°C. The cooling rate is not limited at this stage.
[0176] Then, during the second holding process, the hot-rolled or cold-rolled steel sheet after the second cooling process is heated to a second temperature range of 200~420°C and held in the second temperature range in a manner that satisfies the following formulas (2) and (3).
[0177] In this process, the untransformed austenite is stabilized to ensure the retention of austenite.
[0178] If the cooling stop temperature exceeds 200℃, the formation of martensite within the steel plate (i.e., the distribution of untransformed austenite) becomes uneven, σ1 / γ ave Outside the expected range. There is no specific lower limit for the cooling stop temperature, but in reality it is difficult to set it below room temperature (20°C).
[0179] Equation (2) is a parameter related to the stability of untransformed austenite. If this value does not meet the desired range, the stabilization of austenite becomes insufficient, and during the cooling period to room temperature, a portion of the untransformed austenite transforms into martensite, thus the volume fraction of retained austenite does not meet the desired range. If the second holding temperature is less than 200°C or more than 420°C, or if the middle edge of Equation (2) is less than 9500 or more than 13500, then the amount of retained austenite is less than or equal to the specified value.
[0180] [Mathematical Expression 9] [Mathematical Expression 10] Here, t and t in equations (2) and (3) above f T, T max The following are respectively represented.
[0181] t: Elapsed time [seconds] t f End of stay (in seconds) T: Temperature at time t [K] T max The highest temperature reached during residence [K] (Plating process) When forming an electroplated zinc layer on a steel sheet, known methods can be used. Alternatively, when forming a hot-dip galvanized layer on the surface of the steel sheet, a known plating process can be performed, which involves immersing the steel sheet in a hot-dip galvanizing bath, lifting it, and adjusting the weight per unit area by wiping. The plating process can be performed at any stage. For example, as long as the conditions of the above-mentioned heat treatment process are met, it can be performed during the cooling process (first cooling process or second cooling process), between the cooling process and the holding process (first holding process or second holding process), during the holding process, or after the holding process.
[0182] (Alloying process) When the hot-dip galvanized layer is an alloyed hot-dip galvanized layer, an alloying process to alloy the hot-dip galvanized layer can be performed after the plating process. The alloying process can be performed in any process after the plating process. For example, as long as the conditions of the above-mentioned heat treatment process are met, it can be performed after the plating process and during the cooling process of the heat treatment process, between the cooling process and the holding process, during the holding process, or after the holding process.
[0183] However, in the case of plating or alloying processes, even if the holding time at the specified temperature based on these processes is included, the process is carried out in a manner that satisfies the conditions of the aforementioned heat treatment processes.
[0184] For example, when a plating or alloying process is performed between the cooling and holding processes, or after the holding process, at a temperature of 360-480°C on the steel plate, the holding time during the holding process, combined with the time during the plating and alloying processes when the steel plate reaches 360-480°C, should be controlled to not exceed 600 seconds.
[0185] (Molding process) In the forming process, the steel plate of this embodiment obtained through the above process is formed into a specified shape as required.
[0186] There are no restrictions on the molding method or the shape of the molded part. For example, it can be a car frame component with a closed cross section perpendicular to the length direction, such as a front side beam, a rear side beam, or a side beam.
[0187] (Jointing process) For example, to obtain the closed-section structure described above, the steel plate after the forming process is spot-welded (resistance spot welding) to join with other steel plates. There are no restrictions on the spot welding conditions, but a weld nugget diameter of 3√t to 6√t (t: plate thickness) is preferred. Furthermore, the welding current value, energizing mode, pressure, and welding electrodes used should be selected to achieve this weld nugget diameter. Additionally, the interval between spot welds can be approximately 15 to 50 mm.
[0188] Example By continuous casting, a slab with the chemical composition recorded in Table 1 is obtained. During continuous casting, casting is performed with the values on the left side of the above formula (4) as shown in Table 2A.
[0189] Then, the slab is heated to the slab heating temperature recorded in Table 2A, as shown in Table 2A, and hot rolling including rough rolling and finish rolling is performed.
[0190] In this table, R1 inlet temperature is the inlet temperature of the (n-2)th pass (the 3rd pass counting from the final pass), R1 is the reduction rate of the (n-2)th pass, R2 is the reduction rate of the (n-1)th pass, R3 is the reduction rate of the nth pass (the final pass), R3 outlet temperature is the outlet temperature of the nth pass, t1 is the time between the (n-2)th and (n-1)th passes, t2 is the time between the (n-1)th and (n)th passes, and t3 is the time from the completion of the nth pass to the start of cooling.
[0191] After hot rolling, the steel plate is cooled to the coiling temperature in Table 2A, so that the average cooling rate of 600~750℃ is as shown in Table 2A.
[0192] After pickling, the steel sheet was cold-rolled according to the reduction rate (cumulative reduction rate) in Table 2B. The thickness of the cold-rolled sheet was 1.2 mm.
[0193] For the cold-rolled steel sheet, heat treatment is performed under the conditions shown in Table 2B. Specifically, the sheet is heated to the heating temperature in Table 2B, held (heating process), and then cooled at the average cooling rate in Table 2B to the cooling stop temperature (first cooling stop temperature) (first cooling process), and held at that temperature (first holding process) (here, the cooling stop temperature of the first cooling process = the holding temperature of the first holding process). Then, it is cooled at the average cooling rate in Table 2B (second cooling process). Finally, it is heated and held at that temperature (second holding process).
[0194] The holding time during the heating process in the table refers to the time the steel plate remains at Ac3-20℃ or higher. No. 24 specifies the holding time at the highest reached temperature (±10℃). Additionally, the holding time during the holding process in the table refers to the time the steel plate remains at the holding temperature ±10℃.
[0195] In some examples, a zinc plating layer (electroplated zinc plating or hot-dip galvanized plating) is formed on the surface. In some examples where a hot-dip galvanized plating layer is formed, the hot-dip galvanized plating layer is alloyed to form an alloyed hot-dip galvanized plating layer.
[0196] The electroplated zinc layer is formed after cooling to room temperature following the heat treatment process. The hot-dip galvanized layer is formed by reheating or cooling the steel sheet after the first holding process to 460°C and immersing it in a hot-dip galvanizing bath. The immersion time is 3 seconds. Alloying is performed by heating to the temperature listed in Table 2 after immersion in the hot-dip galvanizing bath and holding for 20 seconds.
[0197] In the "Product" column of the table, CR is an example without a zinc coating, EG is an example with a zinc coating, GI is an example with a hot-dip galvanized coating, and GA is an example with an alloyed hot-dip galvanized coating.
[0198] For the obtained steel plate, the microstructure at the 1 / 4 thickness position is determined using the above method, with σ1 / γ ave The standard deviation σ² of the MS values for the 1 / 8 to 3 / 8 thickness range centered at the 1 / 4 thickness position. For FE-EPMA, JEOL's JXA-8530F was used, with an accelerating voltage of 15kV. TSL's "OIMAnalysis 6.0" was used for analyzing the data obtained via the EBSD method.
[0199] The results are shown in Table 3.
[0200] Furthermore, for the obtained steel plate, a No. 5 tensile test piece according to JIS Z 2241:2022, with the length direction perpendicular to the rolling direction, was used to conduct a tensile test according to JIS Z 2241:2022, and the tensile strength (TS) and elongation (EL) were determined. If the TS is 980 MPa or higher and the EL is 10.0% or higher, it is judged to have high strength and excellent elongation.
[0201] Furthermore, using the obtained steel plate as raw material, a cap-shaped molded body with a curved ridge section of R=5mm and a flat plate serving as the back plate are joined together by spot welding, thereby producing a product made of... FIG. 1A The components forming a closed cross-section structure as shown in the diagram. At this time, as... FIG. 1B As shown, the interval between welding points is 15mm, and the welding current is 5.5 times the diameter of the weld nugget (√t, where t is the plate thickness). Other spot welding conditions are as follows.
[0202] Welding electrode: front end diameter 6mm, front end curvature radius R=40mm, Cr-Cu electrode Power supply: 50Hz single-phase AC Pressure applied: 400 kgf Power-on time: 20 cyc Duration: 5 cycles In the obtained steel components, the chemical composition, metal structure and mechanical properties of the non-welded and non-machined parts are the same as those of the raw materials.
[0203] For the obtained steel component, as shown in Figure 2, under fully constrained lower end (one end), a flat impactor was used to impact it from the upper end (the other end). The impactor weighed 334 kg, and the impact velocity was 11.1 m / s. After the impact, the test specimen was observed. For the general part (non-welded part) and the welded part (HAZ part), the presence or absence of cracks was visually confirmed. The case where no cracks were confirmed was marked as "○: GOOD", and the case where cracks were confirmed was marked as "×: BAD".
[0204] The results are shown in Table 3.
[0205] As shown in Tables 1-3, when using microstructures with specified chemical composition, 1 / 4 thickness position, and σ1 / γ ave In steel components obtained from steel plates with a thickness of 0.20 or less (with non-welded parts and having the same characteristics as the steel plate in non-machined parts), the fracture resistance under axial crushing deformation is excellent.
[0206] Furthermore, when the standard deviation of the MS value σ2 is less than 0.80, the fracture resistance characteristics during axial crushing deformation of the HAZ section are also excellent.
[0207] Industrial availability According to the present invention, a steel plate and a method for manufacturing the same are provided, as well as a steel member obtained using the steel plate that can suppress fracture under axial crushing deformation, wherein the steel plate has high strength and excellent elongation, and can suppress fracture of the member under axial crushing deformation after being formed into a member. Therefore, the present invention has high potential for industrial application.
Claims
1. A steel plate, characterized in that, Contains, by mass % C:0.08~0.20%、 Si: 0.50~1.80%, Mn: 2.00~3.50%, P: below 0.050% S: Below 0.0100% Al:0.001~1.000%、 Ti: 0.001~0.100% B:0.0005~0.0050%、 N: below 0.0100% O: Below 0.0100% Cr:0~1.00%、 Mo: 0~1.00% Cu: 0~1.00%, Ni: 0~1.00% Co: 0~1.00%, W:0~1.00%、 Ta: 0~1.00% Sn: 0~1.00% Sb: 0~0.50%, Nb: 0~0.200% V:0~1.00%、 As: 0~0.10% Zn: 0~1.0000% Ca: 0~0.0100% Mg: 0~0.0100% Zr:0~0.0100%、 Bi: 0~0.0100% REM: 0~0.0100% Hf: 0~0.0100%, and Remaining portion: Chemical composition of Fe and impurities. The microstructure at a position representing 1 / 4 of the plate thickness from the surface towards the thickness direction, expressed as a percentage of area, includes... Residual austenite: 3~10% Ferrite: 0~10%, Pearlite: 0~5%, and Martensite and bainite: 75-97% in total In a cross-section parallel to the thickness direction of the plate, an 80μm × 80μm area centered at the 1 / 4 thickness position in the thickness direction and in a direction perpendicular to the thickness direction is divided into 16 20μm × 20μm portions. When calculating the area ratio of retained austenite in each divided region, the standard deviation of the area ratio of retained austenite in each divided region is set as σ1, and the average is set as γ. ave At that time, σ1 / γ ave It is below 0.
20.
2. The steel plate according to claim 1, characterized in that, The standard deviation σ² of the mass percentage concentrations of Mn [Mn] and Si [Si] at each of the multiple measurement points measured by EPMA in a 35 μm × 50 μm region of the section parallel to the thickness direction of the plate, centered at the 1 / 8 to 3 / 8 thickness position, is less than 0.
80. MS=[Mn]+(2 / 3)×[Si]…(1).
3. The steel plate according to claim 1 or 2, characterized in that, The surface has a hot-dip galvanized layer or an alloyed hot-dip galvanized layer.
4. A steel structural member, characterized in that, It has a steel plate that includes unprocessed parts. The non-processed part contains, by mass%, a percentage of C:0.08~0.20%、 Si: 0.50~1.80%, Mn: 2.00~3.50%, P: below 0.050% S: Below 0.0100% Al:0.001~1.000%、 Ti: 0.001~0.100% B:0.0005~0.0050%、 N: below 0.0100% O: Below 0.0100% Cr:0~1.00%、 Mo: 0~1.00% Cu: 0~1.00%, Ni: 0~1.00% Co: 0~1.00%, W:0~1.00%、 Ta: 0~1.00% Sn: 0~1.00% Sb: 0~0.50%, Nb: 0~0.200% V:0~1.00%、 As: 0~0.10% Zn: 0~1.0000% Ca: 0~0.0100% Mg: 0~0.0100% Zr:0~0.0100%、 Bi: 0~0.0100% REM: 0~0.0100% Hf: 0~0.0100%, and Remaining portion: Chemical composition of Fe and impurities. The microstructure of the unprocessed part at a position representing 1 / 4 of the thickness from the surface in the thickness direction (i.e., the 1 / 4 thickness position) includes, in terms of area %, […]. Residual austenite: 3~10% Ferrite: 0~10%, Pearlite: 0~5%, and Martensite and bainite: 75-97% in total In a cross-section parallel to the thickness direction, an 80μm × 80μm area centered at the 1 / 4 thickness position along the thickness direction and extending 80μm along a direction perpendicular to the thickness direction is divided into 16 20μm × 20μm portions. When calculating the area ratio of retained austenite in each divided region, the standard deviation of the area ratio of retained austenite in each divided region is set as σ1, and the average is set as γ. ave At that time, σ1 / γ ave It is below 0.
20.
5. The steel component according to claim 4, characterized in that, The steel component includes a steel plate having a spot-welded portion, a HAZ (welded area) surrounding the spot-welded portion, and non-welded portions other than the spot-welded portion and the HAZ. The non-machined portion exists within the non-welded portion.
6. The steel component according to claim 4 or 5, characterized in that, In the non-processed section, the standard deviation σ² of the MS values of the concentrations of Mn [Mn] and Si [Si] at each of the multiple measurement points measured by EPMA in a 35μm × 50μm region of 1 / 8 to 3 / 8 thickness centered at the 1 / 4 thickness position, calculated by equation (1), is less than 0.
80. MS=[Mn]+(2 / 3)×[Si]…(1).
7. The steel component according to claim 4 or 5, characterized in that, The surface of the steel plate has a zinc plating layer or an alloyed hot-dip galvanized layer.
8. A method for manufacturing a steel plate, which is the method for manufacturing a steel plate according to claim 1, characterized in that, have: A continuous casting process, through which a slab having the chemical composition described in claim 1 is obtained by continuous casting; In the hot rolling process, the slab is heated to a heating temperature and subjected to hot rolling including rough rolling and finish rolling. After cooling to the coiling temperature, it is coiled at the coiling temperature to obtain a hot-rolled steel plate. The cold rolling process involves pickling the hot-rolled steel sheet and cold rolling it with a cumulative reduction rate of 30-75% as needed to obtain a cold-rolled steel sheet; and The heat treatment process involves subjecting the hot-rolled steel sheet or the cold-rolled steel sheet to heat treatment. In the hot rolling process, The heating temperature of the slab is above 1200℃. When the number of passes in the finishing rolling process is set to n, the initial pass is designated as pass 1, and the final pass is designated as pass n, the inlet temperature of pass n-2 is above 950°C, and the outlet temperature of pass n is above 900°C. In the finishing rolling process, at least one pass of reduction exceeding 25% is performed. The time between each of the (n-2)th and (n-1)th passes, and between the (n-1)th and (n-1)th passes, is 0.2 to 1.0 seconds. The time from the end of the nth pass to the start of the cooling process is 1.0 to 3.0 seconds. The winding temperature is 200~550℃. During the cooling process up to the winding temperature, the average cooling rate between 600 and 750°C is 20°C / s or more. The heat treatment process includes a heating process, a first cooling process, a first holding process, a second cooling process, and a second holding process. During the heating process, the hot-rolled steel plate or the cold-rolled steel plate is heated to a temperature range of Ac3-20℃ to 950℃, and held in this temperature range for 1 to 1000 seconds. During the first cooling process, the hot-rolled steel plate or the cold-rolled steel plate after the heating process is cooled to a first cooling stop temperature in the first temperature range of Ms-50℃ to 550℃ at an average cooling rate of 10℃ / s or more between 650℃ and 550℃. During the first holding process, the hot-rolled steel sheet or the cold-rolled steel sheet after the first cooling process is held in the first temperature range for 20 to 100 seconds. During the second cooling process, the hot-rolled steel sheet or the cold-rolled steel sheet after the first holding process is cooled to below 200°C. During the second holding process, the hot-rolled steel sheet or the cold-rolled steel sheet after the second cooling process is heated to a second temperature range of 200~420°C, and held in the second temperature range in a manner that satisfies the following formulas (2) and (3). Here, t and t in equations (2) and (3) f T, T max They represent the following respectively, t: Elapsed time [seconds] t f End of stay (in seconds) T: Temperature at time t [K] T max : The highest temperature reached during residence [K].
9. The method for manufacturing a steel plate according to claim 8, characterized in that, In the rough rolling process, the slab is subjected to at least three passes with a reduction rate exceeding 20% at a temperature of 1050°C or higher. In the continuous casting process, casting is performed in a manner that satisfies the following formulas (4) and (5). Here, τ, τ1, and T in equations (4) and (5) S (τ), T C (τ), T L f L M L M δ S L S δ D δ Mn D δ Si T represents the following respectively. C (τ) is obtained through equation (5). τ: Elapsed time in seconds since casting began. τ1: T in seconds C (τ) The solidification end temperature T at unit K. δ time T S (τ): Slab surface temperature in Kelvin over time τ T C (τ): Estimated internal temperature of the slab over time τ, in K. T L Solidification onset temperature in Kelvin (K). f L Temperature T C Equilibrium volume fraction of the liquid phase at (τ) M L : in mass% and temperature T C Equilibrium Mn concentration in the liquid phase at (τ) M δ : in mass% and temperature T C Equilibrium Mn concentration at δ under (τ) S L : in mass% and temperature T C Equilibrium Si concentration in the liquid phase at (τ) S δ : in mass% and temperature T C The equilibrium Si concentration at δ under (τ) D δ Mn : with m 2 Temperature T in seconds C The diffusion coefficient of Mn in the δ phase under (τ) D δ Si : with m 2 Temperature T in seconds C The diffusion coefficient of Si in the δ phase under (τ).
10. The method for manufacturing a steel plate according to claim 8 or 9, characterized in that, It also includes a plating process in which a galvanized layer is formed on the surface of the hot-rolled steel sheet or the cold-rolled steel sheet during the first cooling process or the second cooling process of the heat treatment process, between the first cooling process or the second cooling process and the first holding process or the second holding process, during the first holding process or the second holding process, or after the first holding process or the second holding process.
11. The method for manufacturing a steel plate according to claim 10, characterized in that, The zinc plating layer is a hot-dip galvanized layer. The steel plate manufacturing method further includes an alloying process, in which the hot-dip galvanized layer is alloyed after the plating process to form an alloyed hot-dip galvanized layer.
Citation Information
Patent Citations
High strength thin steel sheet having excellent elongation and hole expansibility and method for producing the same
JP2006104532A
High strength steel sheet having excellent workability
JP2007262494A
Semiconductor switch
JP2024053452A
High-strength steel sheet and method for manufacturing same
WO2013051238A1
Cold-rolled steel sheet and hot-dip galvanized cold-rolled steel sheet
WO2018179386A1
